Implementação do REUNI na UTFPR e as particularidades do câmpus de Medianeira - Trevizan, Edevania [UNESP] (2014)
The Program of Supporting for Restructuring and Expansion Plans of Federal Universities - REUNI was presented as one of the main actions of the Lula government to expand the federal universities. Materializing a set of measures developed since 1990 aimed at maximizing the results for education through the ceaseless pursue of efficiency and productivity in public universities. The program was approved by a federal decree and show itself as a structural and curricular reconfiguration of public universities, establishing goals to be implement by public universities based on agreements signed between each university and the Ministry of Education. This research proposes to investigate the process and the context of elaborating the restructuring project of the college education and the rebound produced from it in UTFPR. Identifying the changes produced by union to REUNI and evaluating the context and development of the REUNI in the university. The results were obtained through literature search and documentary analysis. For this, it was examined the processes of elaboration and execution of the plan goals of the university, developing the research by analyzing the academic, administrative and infrastructure categories. With that, it is noticeable that in UTFPR despite of the construction of normative outline aimed to execute the actions, targets and indicators agreed and the opening of new courses, mainly what is referred to the availability of vacancies happen as expected, it was verified a difficulty in achieving the agreed results especially in relation to the number of students, this result failed to achieve the target of 18 students per teacher recommended by the program. The data obtained in the academic implementation of REUNI in UTFPR in relation to enrolled students and graduated students is presented below the agreed. In this way, it can be understandable that albeit the numbers of courses have surpassed the foreseen, the ...